(untitled) (Research, Society and Development, 2022)
Monitoring and treatment of intracranial pressure are extremely important procedures in the management of patients with traumatic brain injury. The monitoring methods currently marketed are invasive and are not suitable for all patients. In addition to the risks offered, they are not available on all services. This study aims to describe the cases of five patients with traumatic brain injury of different severity who underwent noninvasive monitoring of intracranial pressure in the acute phase of the injury, relating the changes identified with the clinical picture presented. Patients showed important changes in intracranial pressure wave morphology, possibly related to the lesions, clinical presentation and therapeutic interventions used.